CODE MIXING USED IN WOMEN MAGAZINE: A SOCIOLINGUISTIC STUDY - Netty Herawati (JURNAL DIMENSI, 2012)
In modern era, mostly people use more than one language to communicate. Therefore, the phenomenon of bilingual or multilngual community is feature of code mixing and code switching. This study concerns of the code mixing used by journalist in women magazine of Nova. The data took from the Magazined which was published on March 12-18th, 2012 . This study found types of code mixing and reasons of code mixing. The types of code mixing consist of lexical mixing, phrase mixing of code, and Indonesian speeling of English sounds. The last is reason why people mixed codes. The reasons are lexical need; it is when the Indonesian word not available such as film and the prestige, such as Talkshow although it is available in Indonesian language.